Application of Failure Mode Effects Analysis (FMEA) Method and Fault Tree Analysis (FTA) Towards Health and Occupational Safety on Jetty Project, Gresik, Indonesia - Mohamad Ferdaus Noor Aulady; Felicia Nuciferani; Satya Wicaksono (JACEE (Journal of Advanced Civil and Environmental Engineering), 2018)
Abstract: Work accident in Indonesia has considerably increased every year. Work accident is often occurred in Construction sector. This is due to lack of proper occupational health and safety system (OHS). By the simple OHS management system, this issue can be improved. This research aim to identify the most fatal and high intensity risk of Jetty Project. Furthermore, this study also identify the risk cause that occur by simple method. Therefore, it will be easier for the company to do risk mitigation. To overcome this issue this research use Failure Mode Effect Analysis and Fault Tree Analysis methods. The results of this research show the most dominant risk priority in the girder bridge construction is the girder fall from during the mobilization. And daydream is the most dominant causes.